Analisis Struktur Balok Non Prismatis Menggunakan Metode Persamaan Slope – Deflection - Setiawan, Agus (Bina Nusantara University, 2011)
Slope – deflection equation method is an analysis method to solve statically indeterminate structure. This method is a simple technique to analyze continuous beam, either prismatic or non prismatic. The technique for analyzing non prismatic beam is based on the prismatic beam concept, but with the introduce of some modification coefficient. These coefficients are available in some textbook discussing about structural analysis. This research has an objective to compare the analysis result of a continuous non prismatic beam, with slope – deflection equation method, and result from a structural analysis program (i.e. SAP 2000 v.11.00). The internal moment at the joints produced from this two method will be compared each other. The results show that there is a small difference resulted in internal moment, obtained from hand calculation with slope – deflection method and from software output. The differences resulted from this two techniques are 2 up to 6%. Based on this result it can be stated that slope-deflection method can be used to analyze statically indeterminate nonprismatic beam with some modification factors. The result obtained is nearly the same with one obtained from commercial softwares.